2018
DOI: 10.1371/journal.pntd.0006263
|View full text |Cite
|
Sign up to set email alerts
|

The association between obesity and dengue severity among pediatric patients: A systematic review and meta-analysis

Abstract: Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 37 publications
0
44
0
3
Order By: Relevance
“…14 However, metaanalysis and systematic review recently enroled 15 studies from 2000 until 2016 reported obesity as a risk factor of severity in children with dengue infection (OR = 1.38; 95% CI:1.10, 1.73). 15 In addition, recent study shown obese patients with dengue infection possess many clinical parameters suggestive of more severe clinical manifestations. 16 Study of obesity in severe dengue infection still rare.…”
Section: Resultsmentioning
confidence: 99%
“…14 However, metaanalysis and systematic review recently enroled 15 studies from 2000 until 2016 reported obesity as a risk factor of severity in children with dengue infection (OR = 1.38; 95% CI:1.10, 1.73). 15 In addition, recent study shown obese patients with dengue infection possess many clinical parameters suggestive of more severe clinical manifestations. 16 Study of obesity in severe dengue infection still rare.…”
Section: Resultsmentioning
confidence: 99%
“…This was not possible in view of only one study with children. Moreover, there might be some extent of interaction with TNF-α -238 G>A or TNF-α -308 G>A and other genes (gen-gen interaction/synergism) or other potential confounding factors such as nutritional status of the patients included [ 16 ]. Hence, findings in this meta-analysis should be interpreted with cautions.…”
Section: Resultsmentioning
confidence: 99%
“…The total score for each study ranged between 0 (the worst) and 9 (the best). As described in a published systematic review [ 16 ], we adapted the cut-off score points as good (≥7), moderate (≥5) and poor (≤4) for study quality assessment. Any discrepancy between the two investigators was resolved by consensus.…”
Section: Methodsmentioning
confidence: 99%
“…Gender and parental education were included as confounders based on observed differences and BMI z-score, as obesity has been previously associated with DHF risk. 12 Participant and parental smoking status were not included because of no observed group differences.…”
Section: Methodsmentioning
confidence: 99%